PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA SMP DENGAN MODEL INKUIRI UNTUK MELATIHKAN KETERAMPILAN PROSES PADA MATERI SISTEM PENCERNAAN MANUSIA - Handayani, Antika Yekti; Nur, Mohamad; Rahayu, Yuni Sri (Universitas Negeri Surabaya, 2015)
Science process learning emphasis on giving learning experience directly to develop competence in exploring and understanding environment scientifically. Science education is purposed for inquiry and do something in order to help the student to get more understanding about environment. The purpose of this development research is to describe the validity, practicality, and effectiveness of science-biology teaching learning package for Junior High School using inquiry model to facilitate science process skills in human digestive system matter. The package was developed using a 4-D model, and it was implemented in 30 students of SMPN 2 Lamongan. The design of this implementation phase was One Group Pretest Posttest Design with a descriptive analysis of data. The validation revealed that the package was in good quality, so it fits to be used as a teaching learning package. Enforceability of lesson plans was also well-categorized. The student?s activities showed the appropriate inquiry learning. The student achievement in pretest was all students not complete, in posttest all students was complete. Average cognitive product were 49,11 and 91,11 in pretest and posttest respectively with N-Gain 0,82. Average cognitive process were 17,46 and 93,73 respectively with N-Gain 0,92. N-Gain analysis results illustrate that the model of inquiry learning process was able to improve students? science process skills because the result obtained are in the high category. Inquiry learning model also influenced students? cognitif leaning outcome, which could complete all aspect of learning objectives. Sensitivity items were between 0,3 up to 1,0. This indicates that all items were sensitive to learning effect. The student respond of this learning was good, and the students were really exciting and this model could facilitate them to learn. The conclusions of this research was the learning package using inquiry model was valid, practise, and effective to improve students? science process skills in human digestive system. Proses pembelajaran IPA menekankan pada pemberian pengalaman belajar secara langsung untuk mengembangkan kompetensi dalam menjelajahi dan memahami alam sekitar secara ilmiah. Pendidikan IPA diarahkan untuk inkuiri dan berbuat sehingga membantu peserta didik untuk memperoleh pemahaman yang lebih mendalam tentang alam sekitar. Penelitian pengembangan yang telah dilakukan bertujuan untuk mendeskripsikan validitas, kepraktisan, dan efektifitas perangkat pembelajaran IPA yang dikembangkan dengan model inkuiri untuk melatihkan keterampilan proses pada materi sistem pencernaan manusia. Jenis penelitian yang digunakan adalah penelitian pengembangan dengan menggunakan model pengembangan perangkat 4-D, uji coba II pada 30 siswa SMPN 2 Lamongan. Rancangan penelitian saat uji coba adalah One Group Pretest-Posttest. Design dengan analisis data secara deskriptif. Hasil validasi menunjukkan bahwa perangkat berkualitas baik, sehingga layak digunakan dalam pembelajaran, keterlaksanaan RPP dikategorikan baik, dan aktivitas siswa sesuai dengan model pembelajaran inkuiri. Hasil belajar siswa pada uji awal (pretest) menunjukkan semua siswa tidak ada yang tuntas, sedangkan pada uji akhir (posttest) semua siswa tuntas. THB produk rata-rata uji awal (pretest) 49,11 dan rata-rata uji akhir (posttest) 91,11 dengan Indeks N-Gain 0,82. THB proses rata-rata uji awal (pretest) 17,46 dan rata-rata uji akhir (posttest) 93,73 dengan Indeks N-Gain 0,92. Hasil analisis N-Gain menunjukkan bahwa model pembelajaran inkuiri dapat melatihkan keterampilan proses siswa, karena hasil yang diperoleh berada pada kategori tinggi. Sensitivitas butir soal seluruhnya menunjukkan peka terhadap efek pembelajaran karena berada antara 0,3 sampai dengan 1,0. Respon siswa terhadap pembelajaran dinilai baru, menarik, dan memudahkan siswa dalam belajar. Simpulan penelitian ini adalah perangkat pembelajaran yang dikembangkan dengan model inkuiri adalah valid, praktis dan efektif untuk melatihkan keterampilan proses pada materi sistem pencernaan manusia.